Fabrication Of Porous Calcium Sulphate By Using Yeast As Pore Foamer - Norridzwan, Ahmad Syamil (Universiti Sains Malaysia, 2022)
Calcium Sulphate has a wide clinical history than most biomaterials applications. It fills bone deficiencies well and resorbs quickly and completely without causing inflammation. Its basic material is cheap and plentiful. Calcium Sulphate can deliver antibiotics, drugs, and growth hormones. Orthopedics and dentistry use it often.Yeast is a biological agent that can be used as a pore foaming agent. This study aims to fabricate porous Calcium Sulphate using different compositions of yeast (0%, 5%, 10% and 15%) that act as pore foamer with different firing temperatures (900ºC, 1000ºC and 1100ºC). CaSO4 was prepared using aqueous precipitation and was calcined at 500°C. Then, the synthesized powder of CaSO4 was mixed and palletized with yeast. The samples were analyzed using diametral Tensile Strength (DTS), apparent porosity test, bulk density test, linear shrinkage, weight loss, Fourier transform infrared spectroscopy (FTIR) for functional groups, and x-ray diffraction (XRD) for phase analysis. Samples fired at 900°C, with samples of 5Y/95CS show the highest DTS reading, which is 2.03MPa then, sample 10Y/90CS with DTS value of 0.84MPa It can be shown that increasing the amount of yeast may decrease the DTS reading and increase the apparent porosity. Based on the morphology analysis, yeast increases pore size, resulting in low DTS with higher apparent porosity of CaSO4.